Ecofeminism: Women's Resistance to the Development of a Geothermal Power Plant Project in Padarincang, Serang Regency - Selvi Sulistiani; Ika Arinia Indriyany (Dealings Foundation Institute, 2024)
This article examines the women's resistance movement in Padarincang District, Serang Regency, against the development of a Geothermal Power Plant, analyzed through an ecofeminist perspective. As human dependence on energy grows, there is increasing pressure to find alternative energy sources, such as geothermal energy, to meet daily needs. The proposed Geothermal Power Plant in Padarincang is part of Indonesia’s commitment to achieving Net Zero Emissions (NZE). However, local resistance emerged due to concerns over the potential economic and environmental impacts of the project. Using qualitative research methods and a case study approach, this study explores how women in Padarincang District contributed to the ecological movement. The findings reveal that the rejection stemmed from a lack of slot thailand community engagement and socialization about the development, leading to fears of environmental degradation. Many locals did not understand that geothermal energy could offer new opportunities for renewable energy. The resistance, particularly from women, gave rise to an ecofeminist movement addressing these environmental issues. This research contributes to the literature on the intersection of gender and environmental concerns, particularly by highlighting the role of women in such movements.